Peningkatan Pelayanan Publik di Kantor Sitem Administrasi Manunggal di Bawah Satu Atap Kabupaten Banyuwangi - Sanjaya, Teguh (Jurnal Administrasi Publik, 2014)
Abstract: Public Service Improvement in Office Systems Administration united under one roof Banyuwangi Regency.This study to describe and analyzes the increase in the public service Samsat Office Banyuwangi and the constraints faced in improving public services in the Office Samsat Banyuwangi. The methods used in this research is qualitative research.The focuses are divided into four aspects namely, efforts to improve public services, Program to improve public services, Internal and external constraints in improving public services. The results showed an increase in public service in the Office of Banyuwangi Samsat is to form the character of the apparatus in accordance with the obligations Samsat carried in serving the public , and shall avoid any infraction . Thus the improvement of public services in Banyuwangi into three parts, namely training programs State personnel resources, services and facilities complement the vigorous action on the violations committed by officers. While the obstacles encountered in the process of improving public services in the Office of Banyuwangi Samsat is about consciousness it self Samsat officer must always be cultivated to minimize the occurrence of the violation. Such as employee discipline problems in complying with written rules, lack of awareness about issues apparatus brokers and the lack of supervision from superiors to subordinates about performance. Keywords: Public Service Improvement, Office Samsat Abstrak: Peningkatan Pelayanan Publik di Kantor Sistem Administrasi Manunggal di bawah Satu Atap Kabupaten Banyuwangi. Penelitian ini bertujuan untuk mendeskripsikan peningkatan pelayanan publik di Kantor Samsat Banyuwangi sekaligus kendala-kendala yang dihadapi dalam peningkatan pelayanan publik di Kantor Samsat Banyuwangi. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif. Fokus ini terbagi menjadi 4 aspek yakni, Langkah-langkah peningkatan pelayanan publik, Program peningkatan pelayanan publik, Kendala Intern dan ekstern dalam peningkatan pelayanan publik. Hasil penelitian menunjukkan peningkatan pelayanan publik di Kantor Samsat Banyuwangi adalah dengan membentuk karakter dari aparatur Samsat sesuai dengan kewajiban yang diemban dalam melayani publik, dan wajib menghindari segala pelanggarannya. Dengan demikian peningkatan pelayanan publik di Banyuwangi kedalam tiga bagian, yaitu mengadakan program pelatihan sumber daya aparatur Negara, melengkapi fasilitas pelayanan dan melakukan tindakan tegas pada pelanggaran yang dilakukan aparat. Sedangkan kendala yang dihadapi dalam proses peningkatan pelayanan publik di Kantor Samsat Banyuwangi adalah mengenai kesadaran petugas Samsat itu sendiri harus selalu di bina untuk meminimalisir terjadinya pelanggaran. Seperti masalah kedisiplinan pegawai dalam menaati peraturan tertulis, kurangnya kesadaran aparat tentang permasalahan calo dan kurangnya pengawasan dari atasan kepada bawahan tentang kinerjanya. Â  Kata Kunci: Peningkatan Pelayanan Publik, Kantor Samsat